Conquering the box office: Factors influencing success of international movies in Russia - Sophia Gänßle; Oliver Budzinski; Daria Astakhova (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2019)
This paper empirically examines factors influencing box office success of international movies in Russia between 2012 and 2016. It adds to existing research on national movie markets, by highlighting the relevance of differences in culture, institutions, language, and consumption habits for movie success. Three groups of success factors are distinguished: distribution related (e.g. budget, franchise), brand and star effects (e.g. top actors or directors), and evaluation sources (e.g. critics and audience rating). We add novel region-specific variables like seasonality, time span between the world and local release, attendance of international stars at Russian movie premieres, and title adaptation to Russian culture. The results indicate that budget, franchise, employment of popular actors and directors, electronic word of mouth and audience ratings exert a significantly positive influence on Russian box office success. However, we find significantly negative effects for international critics and, interestingly, the adaption of movie titles. The main contributions of our study are (i) success factors vary between countries with different cultures, (ii) region-specific factors matter, and consequently (iii) results from one market (e.g. the US) cannot easily be generalised.
Keywords: L10; L82; 330; motion picture economics; movies; entertainment; box office success; Russia